Pentoxifylline alleviates high-fat diet-induced non-alcoholic steatohepatitis and early atherosclerosis in rats by inhibiting AGE and RAGE expression - Wu Jing; Zhao Miao-yun; Zheng Hao; Zhang Hua; Jiang Ying (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the expression of advanced glycation end products (AGEs) and their receptor RAGE in the livers and blood vessels of rats with non-alcoholic steatohepatitis (NASH) and the effect of pentoxifylline (PTX) on liver and artery function in rats with NASH. Methods: Sprague-Dawley rats were fed a high-fat diet for 12 weeks and given PTX by gavage for 4 weeks. The effects of PTX on hepatic liver and vessel function as well as the expression of AGE and RAGE in rats with NASH were assessed. The intima-media thickness (IMT) of the aorta and carotid artery was evaluated using ultrasonography. Results: Serum aspartic aminotransferase (AST) and blood levels of glucose (GLU) were reduced in the PTX group relative to the NASH group. The IMT of the aorta and carotid artery was increased in the NASH group compared with the control group. The IMT was reduced in NASH rats after treatment with PTX. Rats with NASH demonstrated higher AGE and RAGE protein levels in the liver and arteries compared with those of control rats. PTX treatment in NASH rats resulted in a decrease in AGE and RAGE protein levels in the liver and arteries compared with those in the NASH group. Conclusion: Early atherosclerosis was observed in rats with NASH induced by a 16-week high-fat diet. High expression of AGE and RAGE in the livers and arteries of rats with NASH may contribute to the pathogenesis of NASH and early atherosclerosis. PTX showed protective effects on hepatic and arterial function, partially through inhibition of AGE and RAGE expression. Keywords: nonalcoholic steatohepatitis; atherosclerosis; advanced glycation end products receptors; advanced glycation end products; pentoxifylline